SINYAL TRANSDUKSI DARI BROMELAIN SEBAGAI ANTIINFLAMASI PADA UDEMA TELAPAK KAKI TIKUS YANG DISEBABKAN OLEH KARAGEN - Sudjarwo, Sri Agus (Jurnal Kedokteran Brawijaya, 2005)
The signal transduction of bromelain as antiinflamatory in carragenan-induced rat paw edema were investigated. Sprague Dawley Rats were divided into the control groups which were given saline, and bromelain groups which received doses of 10, 20 and 40 mg/kg bromelain (peroral) respectively. This was followed by the administration of 1 % caragenin through the intraplantar route 30 min after administration  bromelain or saline. After the carrageenan injection paw volume, prostaglandin (PGE2) production and cyclooxigenase (COX)-1 and COX-2 expression was measured. The bromelain in doses of 10, 20 and 40 mg/kg showed 11.3; 45.1 and  56.3 % inhibition of paw edema respectively at the  end of three hours. The increase in Prostaglandin (PGE2) levels after carrageenan injection was significantly prevented by preadministration of the bromelain at 20 and 40 mg/kg but not bromelain at 10 mg/kg. Bromelain a dose-dependent inhibited both COX-1and COX-2 activity in carrageenin-induced inflammation. Bromelain inhibited COX-2  than COX-1 stronger activity. These results suggest that antiinflammatory effect of bromelain is due to its ability to inhibit PGE2production could be mediated by inhibition mainly on COX-2 than COX-1 activity. Keywords: Bromelain, Cyclooxigenase, Prostaglandin